Liver transplantation in the Kingdom of Saudi Arabia. Issue 10 (22nd September 2017) - Al Sebayel, Mohammed; Abaalkhail, Faisal; Al Abbad, Saleh; AlBahili, Hamad; Elsiesy, Hussien; Aleid, Maha; Al‐Hamoudi, Waleed
Abstract : The first liver transplantation (LT) in Saudi Arabia was performed in 1991; however, it was not until 1994 that the first structured LT program was launched. Until 1997, all LTs in the Kingdom of Saudi Arabia (KSA) were deceased donor liver transplantations. Programs performing LTs needed the authorization of the Saudi Center for Organ Transplantation (SCOT), which provides the essential support for organ procurement and allocation as well as regulatory support for organ transplantation in the country. Currently, there are 4 LT centers in the KSA. Three centers are in Riyadh, the capital city of KSA, and 1 is in the city of Dammam in the Eastern province. Pediatric living donor liver transplantation (LDLT) began in 1997, while the adult LDLT program started 4 years later in 2001. Currently, more than 2000 LTs have been performed by the 4 centers in the KSA. Over 50% of those were performed at King Faisal Specialist Hospital and Research Center in Riyadh. The outcomes of these transplants have been comparable with the international standards. The aim of this review is to provide an overview of LT in KSA. Liver Transplantation 23 1312–1317 2017 AASLD.